Family Support Team's Efforts in Reduce Stunting: Case Study in Tanah Datar District - Arsia, Lativa; Elasta Putri, Siska; Iswadi; Fadri, Zainal (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2025)
The main issue addressed in this thesis is the high number of stunted children in Tanah Datar Regency. The purpose of this discussion is to describe the methods employed by the Family Assistance Team to reduce stunting, explain the challenges faced by the team, and outline the solutions provided by the PMDPPKB Service to overcome these obstacles. The type of research that the author uses is field research using qualitative research methods through a descriptive analysis approach to obtain data from the problems being studied. The data collection techniques used by the researcher are observation, interviews and documentation. This study uses primary and secondary data sources. Data analysis techniques are carried out by data collection, data reduction, data presentation and verification and drawing conclusions. To check the validity of the data, researchers use triangulation of sources and techniques. From the research conducted by researchers in the field, it can be concluded that TPK has five strategic steps to reduce stunting. First, identify stunting targets. Second, the team provides assistance and coaching to families. Third, carry out communication, information, and education (KIE) to convey important information about stunting to targets. Fourth, the team provides additional food and formula milk that is suitable for children who experience stunting. Finally, compile a report on activities and results achieved to be submitted to the PMDPPKB Service. The obstacles found by TPK in the field are divided into two parts. Internal obstacles include lack of understanding of TPK members, poor coordination between TPK members, and lack of training and facilities for TPK members. While the external obstacles are the education of parents of children diagnosed with stunting, parents who do not accept their children being called stunted,  and the community who are less concerned about preventing stunting. Furthermore, the PMDPPKB Service provides solutions to the obstacles faced by TPK.